Vignettes in Patient Safety Volume 2 - Firstenberg, Michael S.; Stawicki, Stanislaw P. (IntechOpen, 2018)
Over the past two decades, the healthcare community increasingly recognized the importance and the impact of medical errors on patient safety and clinical outcomes. Medical and surgical errors continue to contribute to unnecessary and potentially preventable morbidity and/or mortality, affecting both ambulatory and hospital settings. The spectrum of contributing variables-ranging from minor errors that subsequently escalate to poor communication to lapses in appropriate protocols and processes (just to name a few)-is extensive, and solutions are only recently being described. As such, there is a growing body of research and experiences that can help provide an organized framework-based upon the best practices and evidence-based medical principles-for hospitals and clinics to foster patient safety culture and to develop institutional patient safety champions. Based upon the tremendous interest in the first volume of our Vignettes in Patient Safety series, this second volume follows a similar vignette-based model. Each chapter outlines a realistic case scenario designed to closely approximate experiences and clinical patterns that medical and surgical practitioners can easily relate to. Vignette presentations are then followed by an evidence-based overview of pertinent patient safety literature, relevant clinical evidence, and the formulation of preventive strategies and potential solutions that may be applicable to each corresponding scenario. Throughout the Vignettes in Patient Safety cycle, emphasis is placed on the identification and remediation of team-based and organizational factors associated with patient safety events. The second volume of the Vignettes in Patient Safety begins with an overview of recent high-impact studies in the area of patient safety. Subsequent chapters discuss a broad range of topics, including retained surgical items, wrong site procedures, disruptive healthcare workers, interhospital transfers, risks of emergency department overcrowding, dangers of inadequate handoff communication, and the association between provider fatigue and medical errors. By outlining some of the current best practices, structured experiences, and evidence-based recommendations, the authors and editors hope to provide our readers with new and significant insights into making healthcare safer for patients around the world.